Piece-wise and Max-type difference equations : periodic and eventually periodic solutions - Radin, Michael A. (Michael Alexander) (Boca Raton, FL : CRC Press, 2020)
"Piece-wise and Max-Type Difference Equations: Periodic and Eventually Periodic Solutions is intended for lower-level undergraduate students studying discrete mathematics. The book focuses on sequences as recursive relations and then transitions to periodic recursive patterns and eventually periodic recursive patterns. In addition to this, it will also focus on determining the patterns of periodic and eventually periodic solutions inductively. The aim of the author, throughout this book, is to get students to understand the significance of pattern recognition as a mathematical tool. Key Features Can provide possible topics for undergraduate research and for bachelor's thesis Provides supplementary practice problems and some open-ended research problems at the end of each chapter Focusses on determining the patterns of periodic and eventually periodic solutions inductively Enhances students' algebra skills before moving forward to upper level courses Familiarize students with the topics before they start undergraduate research by providing applications"--
Linear difference equations -- Riccati difference equations -- Piece-Wise difference equations -- Max-type difference equations.
OCLC-licensed vendor bibliographic record.
Keywords: Difference equations; MATHEMATICS / General; MATHEMATICS / Applied; MATHEMATICS / Differential Equations